Chemical mechanisms of dissolution of calcite by HCl in porous media: Simulations and experiment. (November 2018) - Gray, F.; Anabaraonye, B.; Shah, S.; Boek, E.; Crawshaw, J.
Highlights: Pore-scale simulation of dissolution of Ketton carbonate was compared to experiment. Location of wormhole formation highly sensitive to initial conditions. Chemical distributions in core obtained by simulation. Dissolution rate controlled by both transport and chemical equilibrium. Introduced new form of Damkohler number for pore-scale simulations. Abstract: We use a pore-scale dissolution model to simulate the dissolution of calcite by HCl in two different systems and compare with experiment. The model couples flow and transport with chemical reactions at the mineral surface and in the fluid bulk. Firstly, we inject HCl through a single channel drilled through a solid calcite core as a simple validation case, and as a model system with which to elucidate the chemical mechanisms of the dissolution process. The overall dissolution rate is compared to a corresponding experiment. Close agreement with experimental and simulated dissolution rates is found, which also serves to validate the model. We also define a new form of effective Damkohler number which can be obtained from simulated chemical distributions, and show how this gives a more precise measure of the balance of transport and reaction. Secondly, we inject HCl into a Ketton carbonate rock core at high flow rate, which leads to wormhole formation, and compare to experiment. The simulation matches the experimental mass dissolution rate extracted from the micro-CT images, and predicts the resulting morphological changes reasonably well. The permeability change though is greater in the experiment than in the simulation, and this is shown to be due to more elongated wormhole formation in experiment. Possible reasons for this are discussed, including uncertainties in diffusion coefficients, and calcite density variations and micro-porosity in the Ketton grains. The distribution of chemical species from the simulation then permits a detailed understanding of the rate-controlling mechanisms at work, including the relative importance of the H + –calcite and H2 CO3 –calcite dissolution pathways.